How learning a musical instrument affects the development of skills - Adrian Hille; Jürgen Schupp (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Previous research does not teach us much about the role of music for skill development. Learning a musical instrument during childhood may affect educational opportunities by improving cognitive skills, teaching non-cognitive skills or sending positive signals to school teachers. Our study is the first to examine these channels with data from the German Socio-Economic Panel (SOEP). In addition to assessing the duration and intensity of music practice during childhood, the SOEP contains detailed information on parents, which may determine both the decision to follow music lessons and educational outcomes: socio-economic background, personality, involvement in the child's school success and taste for the arts. Using regression-adjusted propensity score matching, we test to which extent these characteristics explain outcome differences between children who have learned a musical instrument for at least 9 years and those who did not. Even after including all of the control variables, cognitive skills of adolescents who followed music lessons during childhood are 0.27 standard deviations above those of their peers. Moreover, these children have better school marks and are more conscientious, agreeable and ambitious. Some of the outcome differences are even larger among children who come from families with lower socio-economic status. The causal effect of learning a musical instrument might be smaller than our estimates due to the potential influence of unobserved characteristics. However, we argue that our strict choice of treatment and control variables may actually lead us to underestimate the true causal effect of learning a musical instrument.
Keywords: J13; J24; Z11; 330